Parametric Hemodynamic 4D Flow MRI Maps for the Characterization of Chronic Thoracic Descending Aortic Dissection - Jarvis, Kelly; Pruijssen, Judith T.; Son, Andre Y.; Allen, Bradley D.; Soulat, Gilles; Vali, Alireza; Barker, Alex J.; Hoel, Andrew W.; Eskandari, Mark K.; Malaisrie, S. Chris; Carr, James C.; Collins, Jeremy D.; et al. (Journal of magnetic resonance imaging, 2020)
Background Systematic evaluation of complex flow in the true lumen and false lumen (TL, FL) is needed to better understand which patients with chronic descending aortic dissection (DAD) are predisposed to complications. Purpose To develop quantitative hemodynamic maps from 4D flow MRI for evaluating TL and FL flow characteristics. Study Type Retrospective. Population In all, 20 DAD patients (age = 60 ± 11 years; 12 male) (six medically managed type B AD [TBAD], 14 repaired type A AD [rTAAD] now with ascending aortic graft [AAo] or elephant trunk [ET1] repair) and 21 age‐matched controls (age = 59 ± 10 years; 13 male) were included. Field Strength/Sequence 1.5T, 3T, 4D flow MRI. Assessment 4D flow MRI was acquired in all subjects. Data analysis included 3D segmentation of TL and FL and voxelwise calculation of forward flow, reverse flow, flow stasis, and kinetic energy as quantitative hemodynamics maps. Statistical Tests Analysis of variance (ANOVA) or Kruskal–Wallis tests were performed for comparing subject groups. Correlation and Bland–Altman analysis was performed for the interobserver study. Results Patients with rTAAD presented with elevated TL reverse flow (AAo repair: P = 0.004, ET1: P = 0.018) and increased TL kinetic energy (AAo repair: P = 0.0002, ET1: P = 0.011) compared to controls. In addition, TL kinetic energy was increased vs. patients with TBAD (AAo repair: P = 0.021, ET1: P = 0.048). rTAAD was associated with higher FL kinetic energy and lower FL stasis compared to patients with TBAD (AAo repair: P = 0.002, ET1: P = 0.024 and AAo repair: P = 0.003, ET1: P = 0.048, respectively). Data Conclusion Quantitative maps from 4D flow MRI demonstrated global and regional hemodynamic differences between DAD patients and controls. Patients with rTAAD vs. TBAD had significantly altered regional TL and FL hemodynamics. These findings indicate the potential of 4D flow MRI‐derived hemodynamic maps to help better evaluate patients with DAD. Level of Evidence: 3 Technical Efficacy Stage: 1 J. Magn. Reson. Imaging 2020;51:1357–1368.